Answer:
a 3 + b 3 = (a + b) (a 2 − a b + b 2 ). Substituting a = x and b = 3 into the formula yields: x 3 + 27 = (x + 3) (x 2 − 3 x + 9).
Step-by-step explanation:
Answer:
456 / 10 = <u>45.6</u>
So the answer lies between <u>45</u> and <u>46</u>.
Answer:
Step-by-step explanation:
Answer:
C. (5x^3-7)(2x^2+1)
Step-by-step explanation:
Given expression is,
10x^5+5x^3-14x^2-7
=10x^5-14x^2 + 5x^3 - 7 (By the commutative property)
=2x^2(5x^3-7)+5x^3-7 (Taking 2x^3 common from first two terms )
=(5x^3-7)(2x^2+1) (Taking 5x^3-7 common from both terms)
\implies 10x^5+5x^3-14x^2-7=(5x^3-7)(2x^2+1)
Hence, Option C is correct
The correct answer is actually choice D.